Analysis of Capital Structure and Non Performing Loans on Financial Performance in the Activity Management Unit (UPK) of Boyolali District in 2022-2023 - Irchani, Ervin; Wibowo, Edi; Astuti, Dewi Saptantinah Puji (Journal of International Accounting, Taxation and Information Systems, 2025)
This research investigates how Debt-to-Equity Ratio (DER), Equity Ratio (ER), Non-Performing Loans (NPL), and Loan Loss Provision (LLP) impact the financial performance, as measured by Return on Assets (ROA), in Activity Management Units (UPK) located in Boyolali Regency. A method of purposive sampling was employed to choose 15 UPKs from various regions within the district. Data analysis employed classical assumption tests and hypothesis testing through F-tests, t-tests, and R-square analysis. Results reveal that while Debt-to-Equity Ratio and Equity Ratio individually do not significantly affect financial performance, Non-Performing Loans and Loan Loss Provision demonstrate significant individual effects. Collectively, all four variables significantly influence Return on Assets, explaining 40.2% of financial performance variation. The study suggests improving credit analysis quality and loan write-off processes while highlighting the need for future research with extended timeframes and broader geographic samples.